Vitamin D, Calcium and Phosphor in Patients with β-Thalassemia Major - Ade Hariza Harahap; Bidasari Lubis; Herman Hariman (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
There has been many reports that patients with β-thalassemia major have bone problems such as thinning of the bone, bone fragility and pathological fractures. For so many years it was believed that the bone problems is mainly caused by marrow expansion due to compenstation of the bone marrow to handle the chronic anaemia and hiypoxia in β-thalassemia major. Recently, there is evidence to suggest that in β-thalassemia major there is hypocalcemia and hypovitaminosis D. So, this study is to clarify if hypovitaminosis D is trully the cause of bone problem in thalassemia. Forty five subjects were recruited in this study, 35 were β-thalassemia major patients and 10 normal subjects as controls. Ten mL of venous blood were taken from median vein for investigations of total vitamin D [25(OH) vitamin D], total calcium and phosphor using the Enzyme-Linked Fluorescent Assay (ELFA), metallochromic dye (Arsenazo III) and chemical reaction of inorganic phosphate with amonium mollybdate respectily. Mean ± SD of vitamin D in β-thalassemia major is 21.28 ± 6.36 ng/ml and in control 34.85 ± 3.50 ng/ml (p<0.05); total calcium in β-thalassemia major is 8.58 ± 0.68 mg/dl and in control 9.22 ± 0.35 mg/dl (p<0.05); and phosphor in β-thalassemia major 3.98 ± 0.53 mg/dl and control 3.89 ± 0.49 mg/dl (p>0.1). There was no significant correlation (r = 0.17, p>0.05), when vitamin D was analysed against calcium for the correlation study,. This study demostrates that there was state of hypovitaminosis D and hypocalcemia in β-thalassemia major but hypovitaminosis D is not the only causative factor of the calcium levels. There should be another factor responsible for the calcium levels in β-thalassemia major and marrow expansion may remain the factors responsible for bone abnomarlities.